ADDITION OF CHLOROQUINE DIPHOSPHATE OR ASCORBIC ACID IN JERSEY BULL SEMEN AND SUBSEQUENT EVALUATION WITH RESPECT TO POST-THAW INCUBATION TIME AND CONCEPTION RATE - SINGH, MADHUMEET; SHARMA, A (The Indian Journal of Animal Reproduction, 2022)
Total 36 ejaculates (6 from each Jersey bull) were used in the study and aliquots were added with Chloroquine diphosphate or Ascorbic acid or served as control. Semen straws from all the groups were analyzed at 0, 1 and 2 h post-thaw incubation at 37°C for percent viability, progressive motility, reaction to hypo-osmotic solution and acrosomal integrity. Following post-thaw incubation, an improvement (p<0.05) in all the evaluated semen parameters was recored in groups with semen additives compared to control. The conception rate was better (p<0.05) using semen fortified with ascorbic acid.